Ice sheet erosion patterns in valley systems in northern Sweden investigated using cosmogenic nuclides - Li, Y. K.; Harbor, J.; Stroeven, A. P.; Fabel, D.; Kleman, J.; Fink, D.; Caffee, M.; Elmore, D. (Purdue University, 2005)
Erosion patterns associated with glaciation of trunk and hanging valley systems in northern Sweden were investigated using cosmogenic nuclide Be-10 apparent exposure ages and inferred nuclide inheritance. Sequences of samples taken across valleys known to have been covered repeatedly by the Fermoscandian ice sheet revealed two primary patterns of erosion. In Vavlavagge the exposure age pattern is consistent with > 2 m of glacial erosion during the last glacial cycle along the entire profile. At Ravtasvaggi, Dievssavaggi and Alisvaggi, exposure ages in the valley bottom contrast with apparent exposure ages two to four times older on the valley sides. The older ages on the valley sides reflect cosmogenic nuclide inheritance due to limited (< 2 m) bedrock erosion of the valley sides during the last glacial cycle. The pattern and scale of erosion in these valleys indicates that glacial valley formation is a result of multiple glacial cycles rather than the result of topographic modification during a single glacial cycle. Initial data comparing hanging valley and trunk valley sites do not show distinct differences in apparent exposure ages. Slightly older ages for samples from hanging valley bottoms may suggest nuclide inheritance indicating lower erosion than in trunk valley bottoms, as would be expected given the marked topographic step between hanging and trunk valleys. Although quantifying the amount of erosion depends on the assumed cosmogenic nuclide inheritance prior to the onset of erosion, the pattern of erosion is independent of this. Hence the observed pattern of cosmogenic nuclide concentrations provides constraints on spatial patterns of erosion and helps to refine understanding of the timing and extent of landform modification by glaciation. Copyright (c) 2005 John Wiley & Sons, Ltd.